Aggressive Angiomyxoma—Report of a Rare Male Buttock Lesion. Issue 8 (August 2018) - Hsieh, Frank; Chuang, Kai-Ti; Wu, You-Ting; Lin, Chih-Hung
Abstract : Summary: Aggressive angiomyxoma is a very rare benign tumor for male population with fewer than 50 cases reported since the description of this tumor. Most documented cases of aggressive angiomyxomas were found in genital, perineal, and pelvic regions in women of child bearing age. We report a case of a massive (> 20 cm) aggressive angiomyxomas in a man who presented with perineal swellings. Macroscopically the mass was highly vascular and lobulated with high similarity to plexiform neurofibroma. Microscopic examination revealed a hypocellular tumor comprising bland oval and spindle-shaped cells along with vessels of varying calibre. The accompanying stroma was myxocollagenous. Immunohistochemical staining showed CD34 and focal estrogen receptors positivity and negative staining for S100, actin, desmin, and progesterone receptors. The histologic and immunohistochemical features favored the diagnosis of aggressive angiomyxoma. Despite the rarity of such tumor in the male population, aggressive angiomyxoma should be considered in the differential diagnosis when encountering chronic para-perineal lesions.